Effect of Environmental Performance, Firm Size, Corporate Social Responsibility on Financial Performance on Manufacturing Companies - Mira Afriani; Yadi Nurhayadi; Ummu Salma Al Azizah (Research Parks Publishers, 2021)
This study examined the relationship between environmental performance, firm size, corporate social responsibility on financial performance on manufacturing companies listed in ISSI over the period 2014-2018. The independent variables were hypothesized- environmental performance, firm size, and corporate social responsibility. While the dependent variable was a financial performance (ROA). Whereas, the data used are secondary data of finance and annual statements derived from the Indonesian Stock Exchange and the company’s official website, as well as the PROPER data, reconstituted from The Ministry of Environment and Forestry. The method used in analyzing data on this research is multiple regression linear with the EViews 10. The results showed that environmental performance had no significant effect on financial performance (ROA), the firm size significantly affected the financial performances (ROA), corporate social responsibility significantly affected the financial performances (ROA). Thus, environmental performance, firm size, and corporate social responsibility affect simultaneously on financial performances (ROA)